THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE, COMPENSATION ON THE PERFORMANCE OF EMPLOYEES OF THE REGIONAL DRINKING WATER COMPANY (PDAM) TIRTO NEGORO SRAGEN REGENCY - Dargitara, Adinda; Surendra, Arya (Universitas Of Surakarta, 2023)
This study aims to determine the effect if motivation (X1), work discipline (X2)and compensation (X3) on employee performance (Y) PDAM Tirto Negoro, Sragen regency eiter partially or simultaneously. This research is aquantitative research using 45 respondents as the research sampe. The analytical technique used in thuis research is multiple linier resegression aanlysis, t test (partial), f test (simultaneous) and coefficient of determination test (R2). The results in this study can be concluded that motivation, work discipline and compensation have a significant effect on the performance of PDAM Tirto Negoro Sragen employees either partially or simultaneously.